Influence of rainfall on foraging behavior of a tropical seabird. (27th December 2021) - De Pascalis, Federico; Austin, Rhiannon E; Green, Jonathan A; Arnould, John P Y; Imperio, Simona; Maugeri, Maurizio; Haakonsson, Jane; Cecere, Jacopo G; Rubolini, Diego
Abstract: Acquiring resources for self-maintenance and reproduction is a key challenge for wild animals, and the methods that individuals employ are, in part, shaped by environmental conditions that vary in time and space. For birds, rainfall may affect behavior, impairing senses and increasing energetic costs, but its consequences on movement patterns are poorly explored. We investigated the influence of rainfall on the foraging behavior of the magnificent frigatebird, Fregata magnificens . This peculiar tropical seabird lacks feather waterproofing and is known to track environmental conditions while searching for food. Thus, its foraging behavior should be highly sensitive to the effects of rainfall. By GPS-tracking chick-rearing adults, we showed that frigatebirds did not avoid areas with rainfall during foraging trips, nor did rainfall influence trip characteristics. However, rainfall decreased time devoted to foraging and increased time spent perching. Moreover, it affected flight mode, inducing birds to fly slower and at lower altitudes. Wind speed, which was not correlated with rainfall, only affected behavior during night-time, with strong winds decreasing time spent perching. Our results indicate that rainfall does not affect the spatial distribution of foraging frigatebirds but does alter fine-scale foraging behavior by reducing flight activity. We suggest that the ongoing environmental change in this region, including an increase in rainfall events, has the potential to impair foraging and negatively affect fitness. Abstract : In wild animals, rainfall can alter activities and increase energetic costs. Magnificent frigatebirds, tropical seabirds unable to waterproof their feathers, might be particularly affected. Using biologging techniques we showed that foraging frigatebirds did not avoid areas with rainfall. Instead, they reduced foraging-related activities and increased time spent perching, waiting for the adverse conditions to pass. Therefore, the predicted increase in rainfall in the tropics has the potential to disrupt foraging activities and affect breeding success.